Intraseptal galanin potentiates scopolamine impairment of delayed nonmatching to sample - Robinson, JK (J Neurosci, 1993)
Galanin coexists with ACh in the basal forebrain and medial septal region. The present study investigated the interactions of the muscarinic receptor antagonist scopolamine and the neuropeptide galanin on an operant spatial delayed non-matching to sample task (DNMTS) in rats. Scopolamine administered both intraperitoneally and microinjected into the medial septum impaired performance on DNMTS. Galanin administered alone into the medial septum did not disrupt DNMTS, but potentiated the disruptive effects of intraperitoneal administered scopolamine. These findings raise the possibility that endogenous galanin may exacerbate cognitive impairments associated with forebrain cholinergic deficits.